Peningkatan Kestabilan Pilar Tambang Bawah Tanah Marmer di PT Gunung Marmer Raya - Purwanto Purwanto (Faculty of Engineering UNHAS, 2020)
PT Gunung Marmer Raya (PT GMR), a room and pillar underground marble mining is located about 73 km to the north from Makassar, in Desa Tabo-Tabo, Kecamatan Bungoro, Kabupaten Pangkep. In the mining location, discontinuities are found as joint structure across the production area. The purpose of this service is to make pillar redesign that can improve the stability of underground mine. These activities start with field observation, determining the rock characteristic through sample testing in the laboratory, classifying the rock mass using Q-system method, up to redesigning a form of implementation to increase the stability of the marble underground mine. According to calculation of rock mass classification using Q-System, the recommended buffering is systematic bolting and fiber reinforced sprayed concrete as thick as 5-6 cm with spacing between bolts of 2.2 meters, or systematic bolting without concrete layering with spacing between-bolt 1.8 meter. Joint monitoring, especially on pillars, need to be done routinely so joint movement could be anticipated for progressive movement. The existing dimensions of pillar 5 m x 5 m in length and width is not recommended due to the safety factor is under 1,0 (unstable condition). Based on observation and analytic calculation, for each pillar height of up to 11 meters the pillar is recommended to redesign with length and width 5 m x 9 m for the chain pillar (safety factor around 1.35-1.49); and 5 m x 12 m for barrier pillars (safety factor around 1.58-1.74). Key Words: Underground mining; room and pillar method; Q-system classification system; pillar stability; marble mining.